1997
DOI: 10.1128/mcb.17.9.5044
|View full text |Cite
|
Sign up to set email alerts
|

Zap1p, a Metalloregulatory Protein Involved in Zinc-Responsive Transcriptional Regulation in Saccharomyces cerevisiae

Abstract: Zinc ion homeostasis in Saccharomyces cerevisiae is controlled primarily through the transcriptional regulation of zinc uptake systems in response to intracellular zinc levels. A high-affinity uptake system is encoded by the ZRT1 gene, and its expression is induced more than 30-fold in zinc-limited cells. A low-affinity transporter is encoded by the ZRT2 gene, and this system is also regulated by zinc. We used a genetic approach to isolate mutants whose ZRT1 expression is no longer repressed in zinc-replete ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
262
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(274 citation statements)
references
References 37 publications
8
262
4
Order By: Relevance
“…A defect in vesicular traffic may lead to a defective copper loading of apoFet3p (7,8). ZAP1 encodes a transcription factor that controls the zinc-regulon (33). While its role in iron metabolism is unclear, a recent study has suggested an interplay between iron and zinc, indicating that the zinc regulon may have effects on iron metabolism (34).…”
Section: Discussionmentioning
confidence: 99%
“…A defect in vesicular traffic may lead to a defective copper loading of apoFet3p (7,8). ZAP1 encodes a transcription factor that controls the zinc-regulon (33). While its role in iron metabolism is unclear, a recent study has suggested an interplay between iron and zinc, indicating that the zinc regulon may have effects on iron metabolism (34).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that additional Mac1p target genes must be properly regulated for normal Cu ion resistance. It is possible that, as in the case of the Zn metalloregulatory factor Zap1p, which regulates the transcription of both the high-and lowaffinity zinc uptake genes in yeast (52), Mac1p regulates the expression of both the high-and low-affinity Cu ion uptake genes and that a Mac1 up1 protein would result in dramatic overexpression of the low-affinity Cu ion transport machinery. Additionally, Cu sensitivity in the MAC1 up1 background could result from an inability to properly regulate other genes encoding proteins that may directly or indirectly protect cells from the toxic effects of Cu ions.…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli (Brocklehurst et al, 1999;Outten et al, 2001), Bacillus subtilis (Gaballa and Helmann, 1998;Gaballa et al, 2002) and Saccharomyces cerevisiae (Zhao and Eide, 1997;Jamison McDaniels et al, 1999;Daniels et al, 2002;Bird et al, 2003) a large number of genes were identified encoding metallo-regulatory proteins that act as zinc sensors and transcriptional activators and/or repressors. Zinc finger-containing transcription factors not only regulate 'zinc-sensitive' genes, but also control their own transcription through a positive autoregulatory mechanism (Lyons et al, 2000).…”
Section: Zinc Participates In Gene Expression Controlmentioning
confidence: 99%